What inspires you to visit our welcoming home? Tourist motivation for visiting rural destinations: The case of Jammu and Kashmir - Raina, Danish Iqbal; Ahmad Bhat, Sajad; Ahmad Dar, Ajaz; Abdulla, Parvez; Ahmad Laway, Shakoor (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
This study investigates the push and pull factors inﬂuencing tourists' motivations to visit the Jammu region of the Union Territory of Jammu & Kashmir, classifying these motivations into key dimensions. Data were collected through a structured questionnaire administered to 380 tourists, selected via simple random sampling. Twenty motivations (10 push and 10 pull factors) were analyzed using one-sample t-tests, paired-sample t-tests, Pearson correlation analysis, mean ranking, and factor analysis. The one-sample t-test showed that both push and pull motives signiﬁcantly exceeded the neutral midpoint on the Likert scale, indicating their strong inﬂuence on travel decisions. The paired-sample t-test found no signiﬁcant diﬀerence between the importance of push and pull factors, while Pearson correlation conﬁrmed a strong positive relationship. Factor analysis revealed three key dimensions: ‘Cultural and Experiential Motivation,’ ‘Environmental and Personal Well-being Motivation,’ and ‘Social and Emotional Motivation,’ with cultural motivation being the most inﬂuential. These ﬁndings suggest strategies for promoting heritage sites, eco-tourism, and community-based initiatives to enhance sustainable tourism in the region. This study contributes to tourism scholarship by providing a deeper understanding of visitor motivations and informing targeted tourism development strategies.